Omega 3 and CLA naturally enhanced levels of animal products: Effects of grass and linseed supplementation on the fatty acid composition of lamb meat and sheep milk - Delmotte C.; Rondia P.; Raes K.; Dehareng F.; Decruyenaere V. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
Changes in agricultural practices and consumption habits are accountable for large modifications in the west-European human diet and partly responsible for a higher prevalence of particular diseases. Reducing the saturated fatty acids (SFA) content of animal products and increasing the poly-unsaturated fatty acids (PUFA), n-3 and conjugated linoleic acid (CLA) yields can effectively help people to meet the new nutritional guidelines. Our experiments showed that linseed supplementation to lambs and ewes make it possible to naturally reach these goals by making the milk and meat fatty acid composition healthier. We investigated the effects of factors such as amount, period, inclusion time and treatment of the linseed supply on animal performances and their product composition. This technique did not modify zootechnical criteria, or the usual commercial qualities of the products. Therefore, it is possible for the agriculture sector to easily develop nutritional products that are naturally enhanced and that meet the needs and expectations of consumers. This represents a real opportunity for farmers and a potential significant improvement in our health.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)